The hypolipidemic, anti-inflammatory and antioxidant effect of Kavolì® aqueous extract, a mixture of Brassica oleracea leaves, in a rat model of NAFLD. (September 2022) - Vornoli, Andrea; Vizzarri, Francesco; Della Croce, Clara Maria; Grande, Teresa; Palazzo, Marisa; Árvay, Július; Pucci, Laura; Gabriele, Morena; Matteucci, Marco; Paolini, Moreno; Longo, Vincenzo; Pozzo, Luisa
Abstract: Herein we characterized the bioactive metabolites of the aqueous extract of Kavolì®, a commercial product composed of a mixture of Brassica oleracea leaves, and assessed its potential ameliorating effects in a rat model of non-alcoholic fatty liver disease (NAFLD). Kavolì® extract showed high levels of bioactive compounds and strong in vitro antioxidant activities. Chlorogenic and neochlorogenic acids were identified as the most representative polyphenols. The administration of brassica extract to steatotic rats significantly ameliorated the levels of blood lipids and transaminases, and lipid content and inflammatory markers in liver. Oxidative stress parameters were significantly improved in both liver and brain of steatotic rats. Moreover, plasma and feces levels of short chain fatty acids (SCFAs) were bring back close to control values by Kavolì® treatment, in spite of high fat diet/streptozotocin (HFD/STZ)-induced alterations. The efficacy of Kavolì® in treating hypercholesterolemia, reducing the level of inflammation and cardiovascular disease biomarkers, steatosis and oxidative stress parameters, as well as the ability in modulating SCFAs levels is probably related to the bioactive compounds of the water extract administered to the rat model of NAFLD. In particular, the ameliorating effects are largely attributable to the high content in polyphenols observed in our study.